Mutual Metabolic Interactions in Co-cultures of the Intestinal Anaerostipes rhamnosivorans With an Acetogen, Methanogen, or Pectin-Degrader Affecting Butyrate Production - Thi Phuong Nam Bui; Henk A. Schols; Melliana Jonathan; Alfons J. M. Stams; Willem M. de Vos; Willem M. de Vos; Caroline M. Plugge (Frontiers in Microbiology, 2019)
The human intestinal tract harbors diverse and complex microbial communities that have a vast metabolic capacity including the breakdown of complex carbohydrates into short chain fatty acids, acetate, propionate, and butyrate. As butyrate is beneficial for gut health there is much attention on butyrogenic bacteria and their role in the colonic anaerobic food chain. However, our understanding how production of butyrate by gut microorganisms is controlled by interactions between different species and environmental nutrient availability is very limited. To address this, we set up experimental in vitro co-culture systems to study the metabolic interactions of Anaerostipes rhamnosivorans, a butyrate producer with each of its partners; Blautia hydrogenotrophica, an acetogen; Methanobrevibacter smithii, a methanogen and Bacteroides thetaiotaomicron, a versatile degrader of plant cell wall pectins; through corresponding specific cross-feeding. In all co-cultures, A. rhamnosivorans was able to benefit from its partner for enhanced butyrate formation compared to monocultures. Interspecies transfer of hydrogen or formate from A. rhamnosivorans to the acetogen B. hydrogenotrophica and in turn of acetate from the acetogen to the butyrogen were essential for butyrate formation. A. rhamnosivorans grown on glucose supported growth of M. smithii via interspecies formate/hydrogen transfer enhancing butyrate formation. In the co-culture with pectin, lactate was released by B. thetaiotaomicron which was concomitantly used by A. rhamnosivorans for the production of butyrate. Our findings indicate enhanced butyrate formation through microbe-microbe interactions between A. rhamnosivorans and an acetogen, a methanogen or a pectin-degrader. Such microbial interactions enhancing butyrate formation may be beneficial for colonic health.